Merleau-Ponty on shared emotions and the joint ownership thesis - Krueger, Joel (Continental philosophy review, 2013)
In “The Child’s Relations with Others,” Merleau-Ponty argues that certain early experiences are jointly owned in that they are numerically single experiences that are nevertheless given to more than one subject (e.g., the infant and caregiver). Call this the “joint ownership thesis” (JT). Drawing upon both Merleau-Ponty’s phenomenological analysis, as well as studies of exogenous attention and mutual affect regulation in developmental psychology, I motivate the plausibility of JT. I argue that the phenomenological structure of some early infant–caregiver dyadic exchanges is best described as involving joint subjects. From birth, some experiences are constitutively social in that certain phenomenal states, such as the positive emotions that arise within these early exchanges, are jointly owned. Along the way, I consider a possible objection. I conclude by considering the explanatory significance of adopting JT.